Instability Mechanism of Extraction Structure in Whole Life Cycle in Block Caving Mine - Zhi-Yuan Xia (Geofluids, 2021)
In the whole life cycle of the extraction structure in block caving mine from the beginning of roadways excavation to the end of ore drawing, there are many factors affecting the stability of the extraction structure. The investigation in the mine site shows that the extraction structure often presents the law of repeated instability. In order to reveal the mechanism of repeated instability of the extraction structure, the whole life cycle of extraction structure can be divided into three stages, namely, the formation stage of extraction structure, the undercutting stage without initial caving, and the ore caving and drawing stage. The three-dimensional finite difference software FLAC3D was used to establish the numerical model of the extraction structure in the whole life cycle in the block caving method. The process of ore caving and ore drawing was replaced by manual excavation of the caving area above the undercut space and applying stress on the major apex. The stress and displacement evolution laws of the extraction structure in three stages of the whole life cycle were studied and compared with the instability characteristics of the extraction structure on mine site. The whole life cycle instability mechanism of the extraction structure in Tongkuangyu mine is revealed; the research results show that the extraction structure near the advancing undercut front is prone to producing compressive stress concentration under the action of the surrounding rock stress arch in the stope; if the rock mass shear failure condition is reached, the instability of the extraction structure occurs. The extraction structure near the advancing undercut front is gradually transferred to the area under the undercut space with undercut increase, and the tensile stress concentration gradually appears in the sidewall of ore loading roadway and the tip of major apex; if the tensile strength of the rock mass in the extraction structure is exceeded, the instability occurs again. It is helpful to reduce the probability of the instability of the extraction structure to promote the overburden ore caving as soon as possible after the undercutting begins.